PELATIHAN PENGUKURAN EMISI GAS KARBON MONOKSIDA (CO) DAN NITROGEN OKSIDA (NOX) PADA KENDARAAN BERMOTOR DI SMA NEGERI 2 BONE - Wahid Wahab, Abdul; La Nafie, Nursiah; Ramang, Musa; Raya, Indah; Hala, Yusafir (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
Training Of Carbon Monoxide (CO) Gas and Nitrogen Oxide (NOx) Measurement Emissions In Motor Vehicles at State High School 2 Bone Abstract. Every year the population in Bone Regency was increased. The increasing population every year has meant the transportation need will be increase because to support mobility and community activities in Bone Regency, Its means that transportation is absolutely necessary. Based on BPS data from Bone Regency, in 2016 the population was 746.973 people. The increasing number of motorized vehicles from year to year will cause air pollution. Environmental conditions in Bone Regency are declining due to high human activities, namely household activities that have reached 14%, industry 18%, commercial 3%, others 9% and means of transportation 56%. To produce good environmental conditions, especially at the location of Senior High School 2 Bone-in Bone Regency, we held community service by introducing and applying and utilizing PEM-9004 instrument to measure carbon monoxide (CO) and nitrogen oxide (NOx) gas emissions in motorized vehicles in particular vehicles belonging to teachers and students at Senior High School 2 Bone. The measurement results showed CO gas emissions on matic motors which were 0.087%, NO gas emissions by 32 ppm and NOx at 33 ppm. While the percentage of CO and NOx gas emissions in duck motors is 0. During the measurement, there was also a decrease in gas emission temperature from 38.6oC to 36.9oC with a testing time of 60 seconds each. Based on the results of the activity data, it is obtained that the percentage of CO and NOx gas emissions of the motorbike is greater than the duck motor of teachers and students at Senior High School 2 Bone. Keywords: PEM-9004, carbon monoxide (CO), nitrogen oxide (NOx), Senior High School 2 Bone Abstrak. Setiap tahun jumlah penduduk di Kabupaten Bone mengalami peningkatan. Semakin meningkatnya jumlah penduduk setiap tahunnya, maka sarana transportasi akan semakin meningkat karena untuk menunjang mobilitas dan aktivitas masyarakat di Kabupaten Bone maka sarana transportasi merupakan kebutuhan yang mutlak diperlukan. Berdasarkan data BPS Kabupaten Bone, tahun 2016 jumlah penduduk sebesar 746.973 jiwa. Meningkatnya jumlah kendaraan bermotor dari tahun ke tahun akan menimbulkan polusi udara. Kondisi lingkungan di daerah Kabupaten Bone semakin menurun karena tingginya aktivitas manusia yaitu kegiatan rumah tangga telah mencapai 14%, industry 18%, komersial 3%, lainnya 9% dan sarana transportasi 56%. Untuk menghasilkan kondisi lingkungan yang asri khususnya di lokasi SMA Negeri 2 Bone Kabupaten Bone maka diadakan pengabdian masyarakat dengan cara pengenalan dan pengaplikasian serta pemanfaatan Alat PEM-9004 untuk mengukur emisi gas karbon monoksida (CO) dan nitrogen oksida (NOx) pada kendaraan bermotor khususnya kendaraan milik guru dan siswa di SMA Negeri 2 Bone. Hasil pengukuran menunjukkan emisi gas CO pada motor matic yaitu 0,087%, emisi gas NO sebesar 32 ppm dan NOx sebesar 33 ppm. Sedangkan presentase emisi gas CO dan NOx pada motor bebek yaitu 0. Selama pengukuran juga terjadi penurunan suhu emisi gas dari 38,6 oC menjadi 36,9 oC dengan waktu pengujian masing-masing 60 detik. Berdasarkan data hasil kegiatan tersebut maka diperoleh bahwa presentase emisi gas CO dan NOx motor matic lebih besar di bandingkan dengan motor bebek milik guru dan siswa di SMA Negeri 2 Bone. Kata kunci: PEM-9004, karbon monoksida (CO), nitrogen oksida (NOx), SMA Negeri 2 Bone